Provision of instructions to drink ad libitum or according to thirst sensation: impact during 120 km of cycling in the heat in men - Claveau, P.; Deshayes, T. A.; Jeker, D.; Pancrate, T.; Goulet, E. D. B. (Applied Physiology, Nutrition, and Metabolism, 2022)
The terms drinking to thirst and ad libitum drinking are used interchangeably, but should they? We investigated the differences in how athletes consumed fluids during exercise when instructed to drink according to thirst or ad libitum. Using a randomized, crossover, and counterbalanced design, 10 males (27 ± 4 y) cycled 120 km (48 ± 4% of peak power, 33 °C, 40% relative humidity) on 2 occasions, while drinking water according to thirst or ad libitum. Participants covered the cycling trials in 222 ± 11 min (p = 0.29). Although the body mass loss at the end of exercise and total volume of water consumed were similar between trials, thirst perception before each sip and the volume consumed per sip were significantly higher with thirst than ad libitum drinking, whereas the total number of sips was significantly lower with thirst than ad libitum drinking. Perceived exertion, rectal temperature, and heart rate were all significantly higher with thirst than ad libitum drinking, but the difference was trivial. In conclusion, thirst and ad libitum drinking are associated with different drinking patterns, but equally maintain fluid balance during prolonged exercise. The terms drinking to thirst and ad libitum drinking can be used interchangeably to guide fluid intake during prolonged exercise. Novelty: • Both strategies are associated with different patterns of fluid ingestion during prolonged exercise, but are equally effective in maintaining fluid balance. • Perceived exertion, rectal temperature, and heart rate are regulated dissimilarly by thirst and ad libitum drinking, but the difference is trivial.